2012
DOI: 10.1071/sr12276
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the clay - cation bond affects soil structure as verified by X-ray computed tomography

Abstract: Non-destructive X-ray computed tomography (µCT) scanning was used to characterise changes in pore architecture as influenced by the proportion of cations (Na, K, Mg, or Ca) bonded to soil particles. These observed changes were correlated with measured saturated hydraulic conductivity, clay dispersion, and zeta potential, as well as cation ratio of structural stability (CROSS) and exchangeable cation ratio. Pore architectural parameters such as total porosity, closed porosity, and pore connectivity, as characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Total porosity and pore connectivity were influenced by cation valence, as might be anticipated from the Schulze-Hardy Rule (Sposito, 2008). A well-developed pore structure was evident in soils having a sufficiently high concentration of exchangeable Ca and Mg, whereas soils dominated by Na and K had isolated pore clusters surrounded by pores filled with dispersed clay particles (Marchuk et al, 2012). Clay dispersion decreased in the order: Na > K > Mg > Ca and, correspondingly, hydraulic conductivity decreased in the reverse order, as reported originally by Quirk and Schofield (1955).…”
Section: Effects Of K and Mg On Soil Hydraulic Conductivitymentioning
confidence: 80%
See 1 more Smart Citation
“…Total porosity and pore connectivity were influenced by cation valence, as might be anticipated from the Schulze-Hardy Rule (Sposito, 2008). A well-developed pore structure was evident in soils having a sufficiently high concentration of exchangeable Ca and Mg, whereas soils dominated by Na and K had isolated pore clusters surrounded by pores filled with dispersed clay particles (Marchuk et al, 2012). Clay dispersion decreased in the order: Na > K > Mg > Ca and, correspondingly, hydraulic conductivity decreased in the reverse order, as reported originally by Quirk and Schofield (1955).…”
Section: Effects Of K and Mg On Soil Hydraulic Conductivitymentioning
confidence: 80%
“…Scanning electron micrographs showed that enrichment with K resulted in the formation of dense, continuous networks of clay particles filling the pore spaces between sand particles (Chen et al, 1983). Marchuk et al (2012) applied computed X-ray tomography to characterize changes in pore architecture as influenced by exchangeable Na, K, Mg, and Ca. Total porosity and pore connectivity were influenced by cation valence, as might be anticipated from the Schulze-Hardy Rule (Sposito, 2008).…”
Section: Effects Of K and Mg On Soil Hydraulic Conductivitymentioning
confidence: 99%
“…Both flocculation and dispersion may occur under certain conditions that could result in enlargement of pores with simultaneous blocking of pore throats, thus reducing the pore connectivity and active porosity. For studying such complex changes in pore structure, X-ray CMT appears to be more appropriate than MIP (Marchuk et al, 2012).…”
Section: Kakuturu and Clarkmentioning
confidence: 98%
“…However, they are not sufficient to understand the clogging mechanism of SFM by NaCl as a deicing salt. Marchuk et al (2012) used x-ray computed microtomography (CMT) and studied the permeability reductions due to permeation with water containing different cations, namely, Na, K, Mg, or Ca. They concluded that CROSS serves as a better indicator of pore structure stability than SAR, particularly for soils containing Ca, Mg, and K, in addition to Na.…”
Section: Kakuturu and Clarkmentioning
confidence: 99%
“…However, the high salinity and sodium (Na) concentrations characteristic of recycled wastewaters pose a significant challenge to their sustainable reuse for crop production (Assouline et al 2015;Laurenson et al 2012;Grismer 2014a, 2014b). Adding to this challenge, several recent studies (Arienzo et al 2012;Buelow et al 2015;Marchuk et al 2013;Rengasamy and Marchuk 2011;Smith et al 2015) have documented deleterious effects on soil hydraulic properties caused by high concentrations of potassium (K) and magnesium (Mg), which are typical of recycled wastewaters (Buelow et al 2015;Laurenson et al 2012;Weber et al 2014). The potential consequences include negative impacts on infiltration, water availability and plant growth.…”
mentioning
confidence: 99%